Pressure ulcers in patients receiving palliative care: A systematic review. (July 2019) - Ferris, Amy; Price, Annie; Harding, Keith
Background: Pressure ulcers are associated with significant morbidity and mortality as well as high cost to the health service. Although often linked with inadequate care, in some patients, they may be unavoidable. Aim: This systematic review aims to quantify the prevalence and incidence of pressure ulcers in patients receiving palliative care and identify the risk factors for pressure ulcer development in these patients as well as the temporal relationship between pressure ulcer development and death. Design: The systematic review is registered in the PROSPERO database (CRD42017078211) and conducted in accordance with the 'PRISMA' pro forma. Articles were reviewed by two independent authors. Data sources: MEDLINE (1946–22 September 2017), EMBASE (1996–22 September 2017), CINAHL (1937–22 September 2017) and Cochrane Library databases were searched. In all, 1037 articles were identified and 12 selected for analysis based on pre-defined inclusion and exclusion criteria. Results: Overall pressure ulcer prevalence and incidence were found to be 12.4% and 11.7%, respectively. The most frequently identified risk factors were decreased mobility, increased age, high Waterlow score and long duration of stay. Conclusion: The prevalence of pressure ulcers is higher in patients receiving palliative care than the general population. While this should not be an excuse for poor care, it does not necessarily mean that inadequate care has been provided. Skin failure, as with other organ failures, may be an inevitable part of the dying process for some patients.